Digital Dynamics: Nurturing Entrepreneurial Spirits in Accounting Students: Dinamika Digital: Membangkitkan Semangat Berwirausaha pada Mahasiswa Akuntansi. - Rizky Nur Aziz; Fityan Izza Noor Abidin (Universitas Muhammadiyah Sidoarjo, 2024)
This research delves into the entrepreneurial aspirations of accounting students, exploring the impact of family environment, self-efficacy, and income expectations, with e-commerce as a moderating factor. Utilizing a sample of 66 respondents from Universitas Muhammadiyah Sidoarjo, data was gathered through questionnaires and processed using SmartPLS. The findings reveal significant positive influences: family environment, self-efficacy, and income expectations all contribute to entrepreneurial interest. Interestingly, e-commerce weakens the influence of family environment while bolstering the effect of self-efficacy on entrepreneurial intentions. Additionally, it diminishes the impact of income expectations on students' entrepreneurial pursuits. These insights provide crucial understanding for educators and policymakers, emphasizing the intricate interplay of personal, familial, and digital factors in shaping the entrepreneurial mindset among future accountants.Highlights : Interconnected Influences: Family, self-efficacy, and income expectations significantly shape entrepreneurial interests among accounting students. Digital Moderation: E-commerce acts as a moderating factor, weakening family influence while strengthening self-efficacy in entrepreneurial intentions. Educational Implications: Insights inform educators and policymakers about the complex interplay of personal, familial, and digital factors, vital for nurturing entrepreneurial mindsets in future accountants. Keywords:Entrepreneurship, Family Environment, Self-Efficacy, Income Expectations, E-Commerce